2016
DOI: 10.4103/0972-5229.182200
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agents\' utilization and cost pattern in an Intensive Care Unit of a Teaching Hospital in South India

Abstract: Background and Aims:High utilization and inappropriate usage of antimicrobial agents (AMAs) in an Intensive Care Unit (ICU) increases resistant organisms, morbidity, mortality, and treatment cost. Prescription audit and active feedback are a proven method to check the irrational prescription. Measuring drug utilization in DDD/100 bed-days is proposed by the WHO to analyze and compare the utilization of drugs. Data of AMAs utilization are required for planning an antibiotic policy and for follow-up of intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
40
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 14 publications
17
40
4
Order By: Relevance
“…1 Moreover AMAs are most frequently prescribed drugs in ICU. 2,11 Increasing multidrug resistance with limited availability of newer agents there is urgent need for vigilant surveillance, stringent infection control as well as rational antibiotic prescription1. 1,15 The clinical setting in the medical ICU warrants the use of drugs from various drug classes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Moreover AMAs are most frequently prescribed drugs in ICU. 2,11 Increasing multidrug resistance with limited availability of newer agents there is urgent need for vigilant surveillance, stringent infection control as well as rational antibiotic prescription1. 1,15 The clinical setting in the medical ICU warrants the use of drugs from various drug classes.…”
Section: Discussionmentioning
confidence: 99%
“…Study tool, data measurement and format of analysis: 2,[6][7][8][9][10] All the patients admitted in ICU during the study period were explained clearly about the purpose and nature of the study and written informed consent was taken before including them in the study. All the patients were interviewed daily.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Betalactams are commonly used AMA and use abundantly in practice. There are many studies who found same result [4,7,[9][10][11][12][13].Beta-lactams are well established AMAs regarding their efficacy and safety that may lead to its widespread use. Pallavi et al found broad-spectrum antibiotic was most common in their study [5].…”
Section: Discussionmentioning
confidence: 71%